Biomechanical analysis of the takeoff of Lithuanian elite long jumpers - Satkunskiene, D.; Stanislovaitis, A.; Radziukynas, D. (8th International Sports Science Conference, Vilnius, 25-26 February 2005, 2005)
The purpose of our study was to analyse the kinematics of the takeoff in the long jump by Lithuanian male long jumpers to identify the biomechanical factors limiting their performance.